Considerations about the facets of prejudice aimed at people with disabilities: Deaflympics and Paralympics - Keske , Henrique Alexander Grazzi; da Silva , Antônio Janiel Ienerich (Seven Editora, 2023)
The object of research deals with issues related to forms of prejudice to be faced if effective social inclusion is to be achieved, as well as comprehensive accessibility for people with disabilities, including discussion about the Deaflympics and Paralympics. The methodology used is based on doctrinal and legal analysis, collated with information provided by civil society organizations dedicated to the segment. The objectives present the search for an adequate denomination, including discussion about the conceptual binomials ableism versus overcoming and poorness versus heroism, as present in the social imaginary directed to people with disabilities. As a partial result, it defends a general coordination of public policies, which assume the character of State policies, which have the character of operating a paradigmatic change, in society itself, to face the problem.DOI:https://doi.org/10.56238/globalhealthprespesc-057